ANALISIS IMPLEMENTASI PROFESIONALISME GURU SEKOLAH DASAR DI KECAMATAN SEMITAU KAPUAS HULU - Utari, Eny Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research was an effort to analyze the Implementation of Elementary Schools Teacher Professionalism at Subdistrict of Semitau Kapuas Hulu.. The data that was collected in this research are; (1) data of pedagogic al competency, (2) data personality competency, (3) data of social competency, and (4) data of professional competency. The result of this research showed that: (1) the implementation of pedagogical competency by the educators of elementary school in subdistrict of Semitau Kapuas Hulu reached, averagely, 73.40% with the category good, (2) the implementation of personality competency by the educators of elementary school in subdistrict of Semitau Kapuas Hulu reached, averagely, 79.08% with the category good, (3) the implementation of social competency by the educators of elementary school in subdistrict of Semitau Kapuas Hulu reached, averagely, 83.3% with the category good, (4) the implementation of professional competency by the educators of elementary school in subdistrict of Semitau Kapuas Hulu reached, averagely, 79.15% with the category good. Key words: Teacher Professionalism, Elementary School